Effect of Nutrient Inputs on Water Quality Change and Phytoplankton Growth in Atsumi Bay - Teuku Mahlil; Takanobu Inoue; Yoshitaka Matsumoto; Shinichi Aoki; Shigeru Kato; Kuriko Yokota; Ernawaty Rasul; Makoto Saga (Journal of Engineering and Technological Sciences, 2018)
Eutrophication in an estuary occurs as an effect of the enrichment of nutrient inputs from rivers. This condition has become one of the most common environmental issues experienced around the globe and especially in Japan. Atsumi Bay is a eutrophic coastal area in Japan. The objective of this research was to analyze the influences of nutrient inputs from the Umeda River into Atsumi Bay on pre- and post-rainfall water quality conditions. This study was conducted from July to October 2010. The results showed a decrease of surface salinity after rainfall indicating that huge freshwater inputs had overlaid the surface layer of Atsumi Bay rather than the bottom layer. Moreover, post-rainfall conditions showed an increase of chlorophyll a as an effect of phytoplankton growth, followed by an increase of particulate nutrients. On the other hand, dissolved nutrients decreased due to uptake by phytoplankton and dilution by freshwater.